2009
DOI: 10.1136/bmj.b2826
|View full text |Cite
|
Sign up to set email alerts
|

Effect of timing of first postnatal care home visit on neonatal mortality in Bangladesh: a observational cohort study

Abstract: Objective To assess the effect of the timing of first postnatal home visit by community health workers on neonatal mortality. Design Analysis of prospectively collected data using time varying discrete hazard models to estimate hazard ratios for neonatal mortality according to day of first postnatal home visit. Data source Data from a community based trial of neonatal care interventions conducted in Bangladesh during 2004-5. Main outcome measure Neonatal mortality. Results 9211 live births were included. Among… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
110
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 119 publications
(116 citation statements)
references
References 31 publications
(30 reference statements)
6
110
0
Order By: Relevance
“…We speculate therefore that the pathway for eff ectiveness of the Hala intervention was largely through improved antenatal contact with LHWs leading to improved childbirth care for mothers, including increased facility births in the hands of skilled attendants, and improvements in some elements of immediate newborn care. 33 The lack of improvement in careseeking for newborn illnesses in the intervention clusters could be related to …”
Section: Discussionmentioning
confidence: 99%
“…We speculate therefore that the pathway for eff ectiveness of the Hala intervention was largely through improved antenatal contact with LHWs leading to improved childbirth care for mothers, including increased facility births in the hands of skilled attendants, and improvements in some elements of immediate newborn care. 33 The lack of improvement in careseeking for newborn illnesses in the intervention clusters could be related to …”
Section: Discussionmentioning
confidence: 99%
“…The study reported higher rates of detection of mothers being pallor during the postnatal visits (p ¼ 0.004); however, it had no impact on identifying and improving other maternal morbidities or improving contraceptive rates. In another study, postnatal visits on days 1 and 2 of life had significant effects on neonatal mortality (infants receiving a visit on day 1 versus none: HR 0.33; 95% CI: 0.23 to 0.46) [227].…”
Section: Postnatal Visitsmentioning
confidence: 99%
“…Lack of access to, and availability of, high-quality EmOC, especially cesarean section, has been considered as a risk factor for intrapartum stillbirths, particularly those associated with prolonged/obstructed labor [227].…”
Section: Lower-segment Cesarean Section (Lscs)mentioning
confidence: 99%
“…The strategy has shown positive results in high mortality settings by reducing newborn deaths and improving key newborn care practices [36,37]. While home births are very common in developing countries, only 13% of women in these countries receive postnatal care in the first 24 hours [36].…”
Section: Ibe Et Al Ann Tropmentioning
confidence: 99%
“…Home care visits should occur on days one and three of a newborn's life, and if possible, a third visit should take place before the end of the first week of life (day seven) [36,37]. This is however not practiced in many developing countries like Nigeria, hence the high neonatal mortality [22,37]. Once delivered, the baby should be cleaned up, clothed and put to breast within the first thirty minutes of life.…”
Section: Ibe Et Al Ann Tropmentioning
confidence: 99%